The molecular era of psychiatry - Castillo Duran, Aitor (2024)
Psychiatry is entering a molecular era in such a way that will be possible to integrate in a scientific manner the genetic expression with brain development and the clinical manifestation of behavior. Synaptic proteomics and molecular genetics will permit the identification of functional roles of proteins at the synaptic level and of susceptibility genes for mental diseases. Psychopharmacology is going to offer faster and more selective treatments for mental disorders fostered by the manipulation of molecular targets at the intraneuronal level. The serotonin system is just a good example of the molecular complexity of the brain and the progress in biological psychiatry.